The Effectiveness of Interactive Google Sites-Based Learning Media on Students' Conceptual Understanding - Haerul Johdi; Gunawan Gunawan; Syahrial Ayub; Kosim Kosim (Indonesian Publication Center, 2024)
This study aims to determine the effectiveness of interactive learning media based on Google Sites on students' understanding of concepts. This research was carried out at SMA Negeri 1 Narmada with the research subject of students in class XI MIPA 5. The data collection instrument used to measure the effectiveness of learning media is a test consisting of 15 multiple-choice questions. The analysis of the effectiveness of learning media was assessed based on the increase in pre-test and post-test results. The results showed that the average pre-test and post-test of students were obtained by 39.80 and 84.71, respectively. Based on this increase, an N-Gain test score of 0.74 was obtained, so interactive learning media based on Google Sites on students' understanding of concepts is included in the criteria and is quite effective. Based on the results of the N-Gain test, it can be concluded that interactive learning media based on Google Sites is quite effective in improving students' understanding of concepts.